The benefits of pollination for a fig wasp - Tarachai Y. (2014)
We describe aspects of the mutualistic relationship between the dioecious SE Asian fig tree Ficus montana and its pollinator, Liporrhopalum tentacularis. Female wasps actively collect pollen, which they later deposit inside receptive figs that they have entered. Inside male figs, we found that the reproductive success of lone females that did not carry pollen was lower than that of females that carried pollen. Figs entered by pollen-free fig wasps were more likely to abort. Furthermore, in those figs that did not abort, there were fewer pollinator progeny than in pollinated figs. When pollen-carrying lone females were prevented from ovipositing in male figs, by having the tips of their ovipositors removed, they appeared to be unharmed, but all the figs aborted. This suggests either that male figs may require oviposition, not pollen, in order to be retained by the trees, or that behavioral changes in the wasps prevented pollination from occurring. ©2008 Balaban.